Moral Value in David Ayer’s “Bright Home” - Fahlevi Reza Natsir,; Gusti Ayu Made Rai Suarniti,; Ni Nyoman Kertiasih, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
TThis study explores the moral values presented in David Ayer’s film "Bright: Home," a significant work that addresses complex social themes through a blend of fantasy and reality. The film serves as an effective medium for analyzing various moral lessons embedded within its narrative. The research methodology comprises three main stages: identifying the data source, data collection, and data analysis. The primary data source includes specific scenes, dialogues, and character interactions in "Bright: Home." Data were collected through detailed observation and subsequently analyzed using descriptive methods based on relevant theories, particularly Ashok Gulla's theory of moral values as outlined in his book "Creating Values in Life." The analysis reveals eight distinct moral values depicted in the film: racism, courage, honesty, loyalty, compassion, kindness, selfishness, and friendship. These values are integral to the film's narrative and thematic structure. The study concludes that these moral values not only enrich the storytelling but also offer important reflections on human behavior and societal issues. Understanding these values can provide viewers with deeper insights into ethical considerations and potentially influence their perspectives and actions.